The use of calcium channel blockers in the treatment of cardiovascular diseases - Đokić Mirjana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Voltage-sensitive calcium channels (L-type) mediate the entry of extracellular calcium into smooth muscle and cardiac myocytes and sinoatrial and atrioventricular nodal cells in response to electrical depolarization. In both smooth muscle and cardiac myocytes, calcium is a trigger for contraction. Calcium channel blockers inhibit calcium channel function. This is a heterogeneous group of agents that includes drugs in the following three classes: phenylalkylamines (verapamil), benzothiazepines (diltiazem) and dihydropyridines (nifedipine, amlodipine, felodipine, isradipine, nicardipine, lercanidipine, clevidipine). Nifedipine and the other dihydropyridine agents are more selective as vasodilators, while verapamil and diltiazem block calcium channels also in the myocardium. Because of these differences dihydropyridines are primarily used as antihypertensive agents, whereas verapamil and diltiazem, due to more pronounced suppression of automatism SA node and AV-conduction, are used as antiarrhythmics. In addition, these drugs are used in the treatment of angina pectoris (drugs of choice in vasospastic angina pectoris), Raynaud's phenomenon, and in treatment of vasospasm after aneurysmal rupture and subarachnoid hemorrhage. Most of adverse effects of these drugs are a consequence of their mechanism of action (vasodilatation and depression of myocardial contractility). These effects are predictable and can be avoided or reduced to a minimum by careful dose titration of drug and by avoiding concomitant use of drugs which can increase these effects.